International Conference on Advancements of Medicine and Health Care through Technology ; 12th-15th October 2016, Cluj-Napoca, Romania : MEDITECH 2016 - Vlad, Simona; Roman, Nicolae Marius (IFMBE proceedings ;, 2017)
This volume presents the contributions of the fifth International Conference on Advancements of Medicine and Health Care through Technology (Meditech 2016), held in in Cluj-Napoka, Romania. The papers of this Proceedings volume present new developments in - Health Care Technology, - Medical Devices, Measurement and Instrumentation, - Medical Imaging, Image and Signal Processing, - Modeling and Simulation, - Molecular Bioengineering, - Biomechanics.